Studying the Effect of Nano Filler on Epoxy Properties used in storage tank Low Carbon Steel Protection - Esmael, Israa Abdulsatar; Ibraheem, Nadia Fakhry; Ahmed , Faris Moayed (Journal of Petroleum Research and Studies, 2020)
In this study a nano epoxy coating had been prepared to be used for the protection of the internal and external surfaces of storage tank (low carbon steel) from corrosion. A polymeric coating was reinforced with fillers such as red iron oxide, Zinc phosphate and nano titanium dioxide (TiO2) which have been used as anticorrosion. Pieces from low carbon steel was picked from storage tank and coated with two layers, the first layer was prepared from organic polymer (epoxy) with red iron oxide, the second layer was prepared from epoxy with (a nano titanium dioxide and Zinc phosphate). The fillers weight percentages were (0, 7, 10 and 13 % wt). The nano epoxy coating gave good results in limiting the corrosion, the corrosion rate results show that the best percentage of additives was (13,10 % wt) in salt solution 1.0 %wt ( NaCl, Na2SO3 and KCl ).The coating samples were immersed for 3 month at 25 OC in gas oil and cutting oil then was characterized using spectroscopic method (FTIR), physical and chemical tests add to characterization of particles size was done by SEM. The samples of TiO2 were characterized by XRD and evaluation of corrosion was made by using static potential test.